2013
DOI: 10.1016/j.actbio.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Element distribution in the corrosion layer and cytotoxicity of alloy Mg–10Dy during in vitro biodegradation

Abstract: The present work investigates the corrosion behaviour, the element distribution in the corrosion layer and the cytocompatibility of alloy Mg-10Dy. The corrosion experiments were performed in a cell culture medium (CCM) under cell culture conditions close to the in vivo environment. The element distribution on the surface as well as in cross-sections of the corrosion layer was investigated using scanning electron microscopy, energy-dispersive X-ray analysis, X-ray photoelectron spectroscopy and X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 43 publications
3
56
1
Order By: Relevance
“…It could be shown that in cell culture environment degradation rates more similar to those observed in vivo could be obtained 8 . Moreover, in this artificial environment additional chemical reactions are taking place, which lead to a very complex degradation environment, also more comparable to the findings in vivo 5,6,[9][10][11] .…”
Section: Introductionsupporting
confidence: 81%
“…It could be shown that in cell culture environment degradation rates more similar to those observed in vivo could be obtained 8 . Moreover, in this artificial environment additional chemical reactions are taking place, which lead to a very complex degradation environment, also more comparable to the findings in vivo 5,6,[9][10][11] .…”
Section: Introductionsupporting
confidence: 81%
“…51,52 On the contrary, a previous study showed that the cell viability of osteoblasts was not reduced below 70% for a Mg-10Dy alloy. 53 The reduced relative metabolic activity of the Mg-10Dy alloy may be attributable to an increased Mg 2þ content in the extract. 53 In vitro experiments have shown increases in pH values during degradation of magnesium alloys because of the production of OH À .…”
Section: Discussionmentioning
confidence: 99%
“…53 The reduced relative metabolic activity of the Mg-10Dy alloy may be attributable to an increased Mg 2þ content in the extract. 53 In vitro experiments have shown increases in pH values during degradation of magnesium alloys because of the production of OH À . 9 The optimal pH of HOB is within the range of 7.0-7.6.…”
Section: Discussionmentioning
confidence: 99%
“…However, these β′ precipitates show no adverse effect on the corrosion rate. In CCM, a protective corrosion film forms on the surface of Mg alloys during corrosion [23]. Moreover, organic materials such as proteins would be adsorbed on the surface of the corrosion film [23].…”
Section: Corrosionmentioning
confidence: 99%
“…Previous work has shown that Mg-10Dy alloy has a low corrosion rate, uniform corrosion behavior and good cytocompatibility [22,23]. However, the mechanical properties of Mg-10Dy alloy are not satisfactory.…”
Section: Introductionmentioning
confidence: 98%